SOLUBILITY ENHANCEMENT OF TELMISARTAN BY VARIOUS TECHNIQUES (International Journal of Food and Nutritional Sciences, 2022)
Aim/Background:-The objective of present research was aimed to intensify the bioavailability of drug Telmisartan by enhancing its solubility. It is a drug that belongs to BCS class II and has high permeability but low solubility, which is an anti-hypertensive agent. As it is low soluble its generally showing poor bioavailability. Materials/Methods:-An effort was made to improve dissolution rate through the preparation of solid dispersions of Telmisartan with water soluble carries like polyethylene glycol and beta cyclodextrin by solvent evaporation method, melt evaporation method, kneading method. Nine formulation like were prepared in the ratio of 1:1, 1:3,1:5(drug : polymer). Results/Discussion:-Evaluation tests like physiochemical parameters, wettability and in vitro dissolution study were done accordingly. All of the polymers were found to be efficient in speeding the dissolution of Telmisartan in solid dispersions as compared to the pure drug. Additional FT-IR spectroscopy, different scanning calorimetry, and X-ray diffractometry investigations were carried out to characterise the drug and solid dispersion. Formulation F9 was found as best among all.